Enzymatic synthesis of N-10-undecenoyl-phenylalanine catalysed by aminoacylases from Streptomyces ambofaciens. (December 2020) - Bourkaib, Mohamed Chafik; Delaunay, Stephane; Framboisier, Xavier; Humeau, Catherine; Guilbot, Jérôme; Bize, Cecile; Illous, Estelle; Chevalot, Isabelle; Guiavarc'h, Yann
Graphical abstract: Highlights: First enzymatic production/purification of 10-undecenoyl-phenylalanine as a powder Successful use of this powder in in-vitro depigmentation of melanocytes cultures S. ambofaciens aminoacylases catalytic properties were screened in various conditions The best enzymatic activity in batch reactor was observed at pH 8 and 45 °C Best improvement in catalytic activity using cobalt (Co 2+ ) as divalent ion Abstract: Due to its physico-chemical and biological activities, N-10-undecenoyl-phenylalanine (C11'F) is one of the most interesting lipoaminoacids used in cosmetic and pharmaceutical industries. Its production is currently based on the Schotten-Baumann chemical reaction, which shows some environmental issues in terms of effluents. As a possible biocatalytic alternative, this study presents the evaluation of the reactional and process conditions allowing the production of C11'F using aminoacylases from Streptomyces ambofaciens culture. These aminoacylases showed the best activity at 45 °C and pH between 7 and 8 with a moderate thermal stability. The influence of substrates concentrations on the kinetic parameters of C11'F synthesis showed a more important impact of the phenylalanine concentration as compared to the 10-undecenoic acid concentration. As a reactional product, C11'F appeared to have an inhibitory effect on the enzymatic N-acylation. Cobalt addition allowed an eleven-fold increase of the reaction rate. Batch reactors were used with free aminoacylases without impact on the final C11'F concentration. For the first time, enzymatically produced C11'F was finally purified at the gram scale as a 99% purity white powder. The evaluation of the biological activity on melanocytes cultures showed the presence of skin lightening activity similar to the one obtained with the chemically produced C11'F.